FORMATION OF THE NEW THEATER IN TIMES OF THE REVOLUTION AND CIVIL WAR ON TEREK - Hubulova, Svetlana Alekseevna (History, Archeology and Ethnography of the Caucasus, 2019)
Abstract. The article is devoted to the problem of the state of theatre life in the Terek region in 1917-1920, which is little studied in the regional historiography. The author introduces into the scientific circulation a corpus of new archival documents, which makes it possible to reconstruct the main activities of local theaters, to consider the influence of Moscow touring groups on the theatrical repertoire and audience preferences in the Terek region. The author dwelled on the difficulties experienced by theater companies in the difficult conditions of the revolution, the Civil War and the post-war devastation. The analysis of the documents allowed us to identify new forms of theatrical art, including workers, amateur and national theatrical societies, which fit well into the concept of educating the “new” Soviet person. In the conditions of the most fierce ideological battles, theaters were given the task of introducing the broad masses to art, who had previously been far from it and preferred simpler forms of leisure. In this regard, the repertoire of theaters was represented not only by classical works but also by revolutionary plays of mediocre quality. By trial and error, the theater acquired a new repertoire in a new environment, a spectator who was to educate and instill a good taste for highly artistic theatrical productions. The role of M. Bulgakov in the development of the proletarian theater is also interesting: the plays written by him had ideological fullness and in quality were much higher than those that were present in the repertoire of local theaters. Thanks to the writer’s efforts, the Ossetian Youth Studio was founded in Vladikavkaz, which became the basis of the future professional theater.